(untitled) (Research, Society and Development, 2022)
Integrative literature review that aimed to identify the strategies internationally developed for the performance of pre-hospital care professionals before patients with advanced disease at the end-of-life and their families. The databases consulted, between September and November 2020, were Scopus, Embase and Web of Science (WoS). The empirical analysis material was compo sed of 35 articles, from which method information and results were extracted using a Google form, organized in a spreadsheet in the Excel program and analyzed by thematic approach. Three categories were constructed, which indicated that families and caregivers of long-stay institutions present fears and anxieties towards pain, dyspnea and cardiac arrest. This fact results in the call of prehospital care services. Professionals, when come across the situation, are afraid to suspend interventions and have limitations in terms of training for end-of-life care. This way, they perform procedures and tend to lead patients to the hospital, where they die. It is suggested, concerning the care with the family, support towards finitude, through the articulation between the services that are part of the urgency and emergency network, which can favor monitoring by home care services or primary health care itself, aiming the permanence at home until death. Furthermore, the investment in information technologies for the sharing of clinical data that facilitate decision-making is shown to be relevant, as well as the approximation with palliative care specialized services.